Penegakan Hukum Keimigrasian Tenaga Kerja Asing Yang Non Prosedural - Natasya Carolina Hitipeuw; Arman Anwar; Veriana Josepha Batseba Rehatta (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The entry of non-procedural foreign workers causes problems in destination countries, including Indonesia.Purposes of the Research: Aims to identify and analyze the implementation of visa-free in Indonesia according to immigration law and to identify and analyze forms of immigration law enforcement for non-procedural foreign workers.Methods of the Research: This research uses a normative juridical method with primary, secondary and tertiary legal materials used in the research. The collection technique is carried out through literature studies in the form of scientific works and literature and others.Results of the Research: The research results show that the visa-free policy implemented by the Indonesian government is regulated in Presidential Regulation Number 21 of 2016 concerning Visa-Free. However, in practice, foreigners who enter Indonesia often violate the terms of the visa-free visit by working without permission. So deported by forced repatriation of foreign workers to their countries of origin. Whereas for foreign workers who commit immigration crimes, Pro Justisia's actions go through a protection process in the form of criminal acts for immigration crimes for non-procedural foreign workers